International Society for Horticultural Science (ISHS) - (:unkn) unknown (My University, 2026)
- Council member (April 2012-present) - Convenor of the V Postharvest Unlimited Conference - Convenor of the X ISHS Peach Conference - Co-convenor of the III Horticulture in Europe Conference - Editrorial Board member of the journal Fruits